Postnatal Growth and Prevalence of Obesity in Infants Born Large-for-Gestational Age during the First 3 years of Life: Personal Experience and Exploration of Current Literature: Postnatal growth in infants born LGA - Alyafei , Fawzia; Soliman, Ashraf T; De Sanctis, Vincenzo; Hamed, Noor; Alaaraj, Nada; Ahmed, shayma; AlKhori, Fatima; Abbasi, Saleha (Acta Biomedica Atenei Parmensis, 2022)
Aims of the study: We evaluated the growth patterns in a cohort of infants (n = 120) born large-for-gestational-age (LGA) [birth weight (Bwt) > 4 kg] from birth to age 3 years of age in comparison with normal age and sex-matched children (WHO). Results: LGA infants had high weight for age Z score (WAZ) at birth that decreased significantly during the first 6 months of life (by a mean of – 0.67 SD) that was followed by significant gain during the following 6 months of life (around + 0.4 SD). These children grew on a higher centile of WAZ with no significant change during the second and third years of life.  The prevalence of obesity (WAZ > 2) increased markedly from 24% at the end of their first year to 34% and 36% at the end of their second and third years of life, respectively.  The mean length for age Z score (LAZ) decreased significantly during the first 6 months (by a mean of -0.9 SD) but was maintained at high centile (> 1 SD) during the second and 3rd years.  The weight for length SDS (WLZ) increased significantly during the first 18 months of life and decreases gradually during the second half of the 2nd year and the 3rd year.   Their head circumference SDS decreased significantly in the first 6 months and then sustained around the 70th centiles (+1 SD) in the following 18 months. Conclusion: Our study showed that in LGA babies obesity increased progressively after the first year of life to reach 36% at the end of the third year. Therefore, it is important to apply the early nutritional intervention to decrease the occurrence of obesity and reduce later cardiometabolic risks